Chemical constituents and bioactivities of two boesenbergia species (Zingiberaceae). - Md. Sukari, Mohd. Aspollah (Faculty of Resources Science and Technology, 2013)
Isolation work on rhizomes of b.rotunda has afforded six flavonoid derivatives; pinostrobin, pinocembrin, alpinetin, sakuranetin, cardamonin and boesenbergin. A. while isolation towards B. armeniaca has led to the isolation of two pyrones; 6-aryl-4-methoxy-2-pyrone and 6-cis-styryl-4-methoxy-2-pyrone.